Patient‐Level Exclusions from mHealth in a Safety‐Net Health System. Issue 2 (1st February 2017) - Hinami, Keiki; Harris, Bhrandon A.; Uriostegui, Ricardo; Jasmin, Wilnise; Lopez, Mario; Trick, William E.
Abstract : Excitement about mobile health (mHealth) for improving care transitions is fueled by widespread adoption of smartphones across all social segments, but new disparities can emerge around nonadopters of technology‐based communications. We conducted a cross‐sectional survey of urban low‐income adults to assess inadequate reading health literacy and limited English proficiency as factors affecting access to and engagement with mHealth. Although the proportion owning smartphones were comparable to national figures, adjusted analysis showed fewer patients with inadequate reading health literacy having Internet access (odds ratio [95% confidence interval]: 0.50 [0.26‐0.95]), e‐mail (0.43 [0.24‐0.79]), and interest in using e‐mail (0.34 [0.18‐0.65]) for healthcare communications. Fewer patients with limited English proficiency were interested in using mobile apps (0.2 [0.09‐0.46]). Inpatient status was independently associated with less interest in text messaging (0.46 [0.25‐0.87]). mHealth exclusions around literacy and language proficiency threaten equity, and innovative solutions are needed to realize mHealth's potential for reducing disparities.